Influence of Biohumus Application for Enhancing Crop Yield and Soil Fertility in Agricultural Diversity: A Review - Rahman, Siti Nurul Aini Abdul; Najihah, Tuan Syaripah (AGRIVITA Journal of Agricultural Science, 2025)
This review provides a concise overview of the findings from a recent study examining the impact of biohumus on agricultural diversity. The global challenges of low crop yields and soil infertility have prompted a longstanding debate. Chemical fertilizers have historically been favored for soil enhancement despite their unknown ecological consequences. Growing awareness of environmental contamination resulting from chemical residues has spurred a shift towards economically and environmentally friendly organic fertilizers. Biohumus, an organic fertilizer derived from the decomposition of organic waste, offers a natural source of trace elements that promote plant growth and soil fertility. Numerous studies have demonstrated that biohumus promotes enhanced vegetative growth and increased yields due to its nutrient-rich composition, specifically tailored to support plant development. Additionally, trace elements and microbes within biohumus contribute to improved soil performance, particularly in infertile agricultural regions. Remarkably, biohumus has been demonstrated to mitigate the adverse effects of abiotic stress on plants by facilitating the release of biostimulants. This comprehensive review aims to disseminate research outcomes on the viability of biohumus as a sustainable alternative to chemical fertilizers in agriculture.